Pengelolaan Kinerja Guru Bersertifikat Pendidik di SMK PGRI 1 Surakarta - Sumarno (Journal of Profession Education, 2021)
This study have two aims to describes: 1) learning administration, 2) learning implementation, 3) learning evaluation, and 4) supervising teacher of teacher educator in SMK PGRI 1 Surakarta. This research is qualitative research with case study design. Data was collected by observation, interview, and documentation. Data validation was done through triangulation technique. Data analysis use Milles and Huberman analysis are data reduction, data display and verification. Results of this research there are two things about: 1) learning administration by teacher of certified educators are teachers prepare learning tools such as syllabi, lesson plans, annual program and semester program, 2) Learning implementation by teacher of certified educators conducted in the form of implementation of assignment learning model and ICT-based learning media, 3) Learning evaluation by teacher of certified educators in the form of product assessment, project assessment, and portfolios assessment, 4) Supervising teacher of certified educators conducted by the principal through providing motivation and guidance so that teachers can produce performance products after teachers get educator certificate.